Iklan Layanan Masyarakat Festival Agribisnis 2014 Provinsi Bali - Ida Bagus Surya Ardhana; Mohamad Tohir (Wimba : Jurnal Komunikasi Visual, 2014)
Bali is a province in Indonesia that has Hindus people as a majority. Many Hindus in Bali make Bali become a province that so consumptive of fruit because every offerings that made for the ceremony were made by fruit.Fruit that sold in Bali were not only local fruit but also imported. Unfortunately many peoples in Bali still using and consuming the imported fruit for their dailly routine.After seeing this problem, Dinas Pertanian Tanaman Pangan in Bali made a festival to bring information about the usage and excess of holticultura in. But still many farmer as the participant in this festival and Baliness people didn't know because the promotion media about this festival was still not too much to inform all of them.By using interview, observation, and literature writer get the data and analysis to make the concept and the scenario design for public service ad film.Using Television Commercial as the media that can reach every circle from Baliness people to farmer in Bali, expecting the information about Festival Agribisnis can be informed correctly and also using economical approach can changes people paradigm about local fruit that was healty, cheap, and can help economic matters in Bali.